Dampingan Komunitas Pengusaha Tahu Melalui Pemanfaatan Bungkil Kedelai menjadi Kerupuk untuk Meningkatkan Nilai Jual Bungkil Kedelai di Desa Purwodadi - Lilit Biati; Sofi Faiqotul Hikmah (LPPM Universitas Yudharta Pasuruan, 2020)
Purwodadi Village is a village in the Banyuwangi Regency which is located in the central region, less than 48 km from the center of the regency administration to the west. Along the way to the village of Purwodadi brought by the expanse of rice fields. The economy of Purwodadi Village residents is concentrated in the agricultural sector with a livelihood of 800 people and around 615 farm workers. soybean meal is a potential that can be developed to increase farmers, especially tofu production in Tempurejo Hamlet, Purwodadi Village. This soybean cake cracker product has been promoted directly by the Head of Purwodadi Village for developed communities, starting with PKK mothers, housewives who want to open an entrepreneur. This program can run successfully because it is supported by the natural potential produced by the pulp that is the main ingredient of this program. Can be used to improve the economy of the Purwodadi Village community. From some of the programs that we have done during the implementation of community service programs in the Purwodadi Village community. The community is needed by the community to help advance and prosper the Purwodadi Village.